2009
DOI: 10.1128/iai.01186-08
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniaeCapsular Serotype 19F Is More Resistant to C3 Deposition and Less Sensitive to Opsonophagocytosis than Serotype 6B

Abstract: The polysaccharide capsule is a major virulence mechanism of Streptococcus pneumoniae, shielding the bacterium from phagocytes. Capsule types may differ in their abilities to resist immune defense. Antibodymediated complement activation and opsonophagocytosis are crucial in protection against pneumococcus. Conjugate vaccine trials suggest imperfect protection against 19F. We have previously shown that significantly more anti-19F than anti-6B antibody is needed for killing in the opsonophagocytic assay (OPA). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 62 publications
5
72
0
4
Order By: Relevance
“…We have previously found that pneumococcal isolates of certain serotypes, such as 1 and 5, associated with invasive disease were particularly resistant to complement deposition and opsonophagocytic killing, while serotypes such as 6B and 23F, associated with carriage, were more sensitive to deposition of C3 and opsonophagocytosis (30,31). We found significant variation in the magnitude of complement deposition between isolates expressing the same capsular serotype, suggesting a role of serotype-independent factors in the outcome of this particular interaction.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…We have previously found that pneumococcal isolates of certain serotypes, such as 1 and 5, associated with invasive disease were particularly resistant to complement deposition and opsonophagocytic killing, while serotypes such as 6B and 23F, associated with carriage, were more sensitive to deposition of C3 and opsonophagocytosis (30,31). We found significant variation in the magnitude of complement deposition between isolates expressing the same capsular serotype, suggesting a role of serotype-independent factors in the outcome of this particular interaction.…”
mentioning
confidence: 74%
“…The functional activity of serum antibodies was measured by standard opsonophagocytic killing assay (40) using differentiated HL-60 cells (promyelotic leukemia cells, CCL240; American Type Culture Collection, Rockville, MD), as described previously (30). Shortly thereafter, polymorphonuclear cells were allowed to phagocytose bacteria in the presence of serum pools containing anticapsular antibodies and baby rabbit complement (PeelFreez Biologicals/Dynal) or, as a control, complement only.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…National IPD surveillance data from the UK found that the majority of vaccine failures among the PCV7 serotypes were due to serotypes 6B and 19F in the post-PCV7 period [19]. Vaccine failures related to serotype 19F may be due to resistance to complement deposition and lower sensitivity to opsonophagocytic killing [25]. Inability to effectively clear nasopharyngeal carriage of serotype 19F in children may translate into a lack of "herd protection" against serotype 19F amongst adults.…”
Section: Discussionmentioning
confidence: 99%